Burning to read: English fundamentalism and its reformation opponents - Simpson, James (Belknap Press of Harvard Univ. Press, 2007)
Hundred years of biblical violence -- Good Bible news -- Salvation, reading, and textual hatred -- The literal sense and predestination -- Bible reading, persecution, and paranoia -- History as error -- Thomas More and textual trust -- The tragic scene of early modern reading